Plant anatomy: history and future directions Elucidating leaf anatomical traits in Vereda plants: different survival strategies - Somavilla, Nádia Sílvia; Montenegro, Thaís Franco [UNESP]; Rossatto, Davi Rodrigo [UNESP]; Kolb, Rosana Marta [UNESP] (FapUNIFESP (SciELO), 2024)
Vereda (palm swamp) is a savanna vegetation type widespread in the Cerrado. This environment is characterized by high irradiance levels and waterlogged soils for part of the year, resulting in hypoxic conditions, organic matter accumulation, and nutrient limitation. Due to these characteristics, we expect leaf scleromorphism to be the predominant pattern in the community, thus ensuring the survival of Vereda plants in these harsh environments. We examined the leaves of 14 species in Vereda Grande in central Brazil to identify their anatomy. We also analyzed the light availability and edaphic aspects of the soils in which these plants grow. We found high irradiance and soils which were rich in organic matter but low in nutrients; these factors limit plant growth given the elevated aluminum values and low pH (mean of 3.6). Most species had thick leaves with a thick cuticle, a well-developed mesophyll, calcium crystals, phenolic compounds, and sclerenchyma. These results corroborate the expected pattern of scleromorphism predicted by the environmental conditions to which Vereda plants are subjected. Chelonathus alatus did not show a leaf scleromorphic pattern and avoided stress in the dry period by losing its shoots.
Keywords: Cerrado; leaf emergence; scleromorphism; soil chemical analysis; stress avoidance strategy